Performance of EQ-5D, howRu and Oxford hip & knee scores in assessing the outcome of hip and knee replacements. Issue 1 (December 2016) - Benson, Tim; Williams, Dan; Potts, Henry
Abstract Background We aimed to compare the performance of EQ-5D-3 L andhowRu, which are short generic patient-reported outcome measures (PROMs), in assessing the outcome of hip and knee replacements, using the Oxford Hip Score (OHS) and the Oxford Knee Scores (OKS) for comparison. Methods Outcome was assessed as the difference between pre-surgery and 6-month post-surgery scores. We used a large sample from the NHS PROMs database, which used EQ-5D-3 L, and a small cohort of patients having the same operations collected by MyClinicalOutcomes (MCO), which usedhowRu . Both cohorts completed the OHS (hips) or the OKS (knees). Results The change (outcome) between pre-op and post-op scores as measured byhowRu was greater than that measured by EQ-5D, relative to that measured by OHS or OKS. For hip replacements, the correlation for change measured byhowRu and OHS wasr = 0.77 (0.66–0.85). The corresponding correlation for change measured by EQ-5D Index and OHS wasr = 0.64 (0.63–0.64). For knee replacements the correlation between change inhowRu and OKS wasr = 0.86 (0.75–0.92); between EQ-5D Index and OKSr = 0.59 (0.58–0.60). Conclusions For hip and knee replacement, the outcome measured byhowRu was more highly correlated with that measured by the condition-specific Oxford Hip and Knee Scores than were EQ-5D Index or EQ-VAS. The magnitude of change before and after surgery was also greater.